2016
DOI: 10.3390/ani6110075
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Breeding Stock among Australian Purebred Dog Breeders, with Particular Emphasis on the Dam

Abstract: Simple SummaryOne of the most important factors influencing the health and welfare of puppies is the decision made by the breeder on which dam and sire they will breed from. Unfortunately, our understanding of what dog breeders consider important when selecting their dogs, particularly the dam, is limited. In order to bridge this gap, we conducted an online survey of Australian purebred dog breeders. We identified four major factors that the breeder considered important in relation to the dam: Maternal Care; O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…A 2004 study of Dutch Boxer breeders [ 75 ] indicated that 32% of the breeders utilized genetic information, expressed as an odds ratio of particular sire-dam combinations producing deleterious health traits, in their mate selections. A recent report assessing selection practices among Australian dog breeders indicated that the “genetics and health” attribute of potential dams was one of the top four decision components [ 76 ]; despite this weighting in dam selection some breeders failed to practice health screening, including for CHD. As selection tools for health characteristics improve, using those will demonstrably improve the health of dogs.…”
Section: Discussionmentioning
confidence: 99%
“…A 2004 study of Dutch Boxer breeders [ 75 ] indicated that 32% of the breeders utilized genetic information, expressed as an odds ratio of particular sire-dam combinations producing deleterious health traits, in their mate selections. A recent report assessing selection practices among Australian dog breeders indicated that the “genetics and health” attribute of potential dams was one of the top four decision components [ 76 ]; despite this weighting in dam selection some breeders failed to practice health screening, including for CHD. As selection tools for health characteristics improve, using those will demonstrably improve the health of dogs.…”
Section: Discussionmentioning
confidence: 99%
“…And yet surprisingly little progress has been made in characterizing early maternal style or documenting its effects on later offspring behavior, temperament, and outcomes. Questionnaire studies reveal that dog breeders attach little to no importance to maternal care when considering breeding stock (Leroy et al, 2007 ; Czerwinski et al, 2016a ). However, as results from the broader animal literature indicate that maternal care is extremely important, understanding its effects in dogs specifically is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies (e.g. Czerwinski et al 2016 [13]), suggest that information on dam selection for breeding is poor, and that dams are often selected primarily on their temperament and level of maternal care.…”
Section: Introductionmentioning
confidence: 99%
“…Although the dam and the sire contribute equally to the genetics of each of their puppies, dog breeders may use very different criteria for the selection of male and female parents. For example, a recent study by Czerwinski et al [13] investigated the attitudes and priorities of registered dog breeders towards dam and sire selection. The participants in this study indicated that, in sire selection, conformation, size, pedigree, and temperament are the primary considerations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation